«The black room» the Russian foreign Ministry against Napoleon - D. E. Larin (Vestnik MGIMO-Universiteta)
This article deals with the successful activity of the Russian Empire cryptographers against Napoleon and his troops. Also some organizational work aspects of interception of French army cipher messages are considered.